Ethnoecologist and Land Management of Durian Plants under The Agroforestry System - Meity Melani Mokoginta; Terri Repi; Dewa Oka Suparwata; Robby Rempas; Talha Dangkua (Jurnal Ilmu Pertanian Indonesia, 2025)
Ethnoecology is a science that studies the relationship between humans and the environment. This relationship is related to the use of natural resources around them to continue life using local wisdom, namely the agroforestry system. Ecologically, economically, and socially, the agroforestry system planting patterns can help reduce soil fertility degradation due to human activities that exceed the carrying capacity of the land. The aim of the research was to determine land management and manifestations of land management for durian plants that implement the agroforestry system. The research used qualitative methods with techniques namely collecting data, analyzing data, and drawing conclusions. Data collection used snowball sampling techniques with an unlimited number of respondents. The results explain that (1) land management, tillage, fertilization, crop rotation, and fallow periods on durian plantations have not been managed optimally, resulting in the production of durian plants not being optimal; (2) the manifestation of land management is divided into two, namely traditional and semi-traditional agroforestry systems and these two systems have differences in land management, namely organic and non-organic. Keywords: agroforestry systems, durian, ethnoecology, land management